Tests of articulation in Kannada - Rama Mohan Babu P; Rathna N; Ramesh Bettageri (Journal of All India Institute of Speech and Hearing, 1972)
Uptil now no articulation tests, standardized or otherwise, are available inKannada. Articulation tests such as that of Templin-Darley's and Milisen's areavailable in English, but they cannot be used with people who speak languages otherthan English. There is a dire necessity of standardized articulation tests in all languagesas shown by the results of the following study. A nation-wide survey of PublicSchool Speech Clinicians in U.S. conducted by W. Johnson et al., in 1952 showedthat 90.5 per cent of the total case load have articulation problems. So we are presentingtwo procedures for describing and assessing an individual's articulationpatterns.